Improved photocatalytic H2 production assisted by aqueous glucose biomass by oxidized g-C3N4. (9th August 2018) - Speltini, Andrea; Scalabrini, Andrea; Maraschi, Federica; Sturini, Michela; Pisanu, Ambra; Malavasi, Lorenzo; Profumo, Antonella
Abstract: Chemically modified g-C3 N4 for the photocatalytic H2 evolution from water was explored. Bulk g-C3 N4 was treated in hot HNO3 aqueous solution to obtain the oxidized material (o-g-C3 N4 ), tested in water containing glucose as model water-soluble sacrificial biomass, using Pt as co-catalyst, under simulated solar light. The behaviour of o-g-C3 N4 was studied in relation with catalyst amount, Pt loading, glucose concentration. Results showed that H2 production is favoured by increasing glucose concentration up to 0.1 M and Pt loading up to 3 wt%, and it resulted strongly enhanced using small amount of o-g-C3 N4 (0.25 g L −1 ). o-g-C3 N4 possesses superior photocatalytic activity (∼26-fold higher) compared to pristine g-C3 N4, with H2 evolution further improved by ultrasound-assisted exfoliation and evolution rates up to ca. 1370 μmol h −1 per gram of catalyst, with excellent reproducibility (RSD < 6%, n  = 3). Significant production was observed also in river water and seawater, with results far better (up to ca. 2500 μmol g −1 h −1 ) compared to commercial AEROXIDE ® P25 TiO2 under natural solar light. Graphical abstract: Image 1 Highlights: Oxidized g-C3 N4, a new cheap catalyst for H2 photoproduction from aqueous glucose. 26-folds improvement of H2 production compared to the as-prepared catalyst. 5-folds higher H2 production under natural sunlight than commercial P25 TiO2 . H2 evolution from raw river and seawater superimposable to that in distilled water. Real applicability of modified g-C3 N4 for green H2 photoproduction.